Leveraging Smart Accounting Technologies for Sustainable Public Financial Management in Osun State, Nigeria (Journal of Management and Social Sciences, 2026)
Studies affirm that many countries of the world have successfully adopted AI and IoT for public financial management (PFM) which is vital for good governance in Nigeria. This paper, therefore, examines how smart accounting technologies, especially Artificial Intelligence (AI) and Internet of Things (IoT) could be leveraged to revolutionise public financial management systems and support sustainable governance outcomes in Osun State of Nigeria. The study adopts a quantitative survey research design and employed primary data collated through the structured questionnaire distributed personally and online to respondents in Osun State, Nigeria. A stratified sampling technique was used to select the sample of 360 participants from the State Ministries, Departments, and Agencies (MDAs). The collated data were analysed using frequency distribution, mean and standard deviation. Findings disclose that in Osun State manual PFM system still dominates, causing inefficiencies in accuracy, timeliness and accountability. The results also reveal that the IT infrastructure is weak but technical skills are high. Notwithstanding, the majority of the respondents supported the claims that AI and IoT have the potential impact to increase reporting quality and timeliness, improve resource allocation and fiscal discipline, and fortify audit trails and accountability of the State. This paper concludes that the stakeholders in Osun State are aware of and optimistic about the incorporation of advanced technologies like artificial intelligence and the 'Internet of Things' into the State financial management systems, but the main constraint is the infrastructure not human capacity. This study however recommends the creation of a digital policy with clear deadlines and training materials to direct the use of AI and IoT in public financial management in the State.    KeywordsArtificial Intelligence, ‘Internet of Things’, Osun State, public financial management, smart accounting technologies